Semi-synthesis of a HGF/SF kringle one (K1) domain scaffold generates a potent in vivo MET receptor agonist1. Issue 3 (16th March 2015) - Simonneau, Claire; Bérénice Leclercq; Mougel, Alexandra; Adriaenssens, Eric; Paquet, Charlotte; Raibaut, Laurent; Ollivier, Nathalie; Drobecq, Hervé; Marcoux, Julien; Cianférani, Sarah; Tulasne, David; de Jonge, Hugo; et al.
<x xml:space="preserve">Abstract</x> Clustering of synthetic biotinylated K1 domain from HGF/SF by streptavidin is sufficient to generate a potent MET agonist.